The cytomorphologic comparison between rehydrated air-dried and conventional wet-fixed pap smears - Krit Jaiwong (2018)
Objective: To compare the cytomorphologic quality of the cervical (Pap) smears between two fixation techniques, rehydration of air-dried smears (AD) versus wet fixation (WF). Material and Method: Paired-cervical smears (AD and WF) from 172 women who underwent cervical cytology screening at Chiang Mai University Hospital between August 2004 and September 2004 were prospectively evaluated for the cytologic parameters and the staining qualities. Results: The mean age of the 172 women was 41.7 years (± 2 SD 18.1), 27 women (15.7%) were postmenopausal. Absence of red blood cells in the smear background was significantly more frequent in AD smears than in WF specimens (p = 0.0006). Air-drying artifact was more frequent in AD smears compared to those of WF (p = 0.036) but was of only mild degree in all cases. There was no significant difference between AD and WF smears in the cytoplasmic quality including distinctness of cell border (p = 0.30) and satisfactory staining (p = 0.054). For the nuclear morphology, there was no significant difference between both fixation techniques in the distinctness of nuclear border (p = 0.26) and chromatin crispness (p = 0.23) of the endocervical nuclei. In squamous nuclei, AD smears had higher frequency of indistinct nuclear border and hazy chromatin compared to WF smears (p = 0.003 each). However, these were observed in only mild degree and did not affect the cytologic interpretation. Conclusion: The quality of AD smears was slightly inferior to WF smears but was still satisfactory for cervical cytology. AD technique may be acceptable as an alternative to wet fixation in cytologic cervical cancer screening.